Flash Glucose Monitoring: Differences Between Intermittently Scanned and Continuously Stored Data. (March 2018) - Pleus, Stefan; Kamecke, Ulrike; Link, Manuela; Haug, Cornelia; Freckmann, Guido
The flash glucose monitoring system FreeStyle Libre (Abbott Diabetes Care Ltd., Witney, UK) measures interstitial glucose concentrations and continuously stores measurement values every 15 minutes. To obtain a current glucose reading, users have to scan the sensor with the reader. In a clinical trial, 5% of the scanned data showed relative differences of more than ±10% compared with continuously stored data points (median −0.5%). Such differences might impact results of studies using this system. It should be indicated whether scanned or continuously stored data were used for analyses. Health care professionals might have to differentiate between data reports from clinical software and the scanned data their patients are provided with. Additional information on these differences and their potential impact on therapeutic decisions would be helpful.